PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP BIAYA MODAL EKUITAS (Studi Kasus pada Perbankan) - Nur Hidayati Falah; Wahyu Meiranto (Diponegoro Journal of Accounting, 2017)
The objective of this study is to examine the effect of intellectual capital disclosures on cost of equity capital. In this research, cost of equity capital was measured by Ohlson model which had been modified by Random Walk Model, while Ulum (2011) index were used to measure intellectual capital disclosures.This study used purposive sampling method in data collection.  Data were collected using secondary data of 34 banking companies that published annual report at IDX website in 2012-2015. The result showed that intellectual capital disclosures had significant effect on cost of equity capital. This study also used two control variables, size and leverage. From two selected control variables, size and leverage has no significant effect on cost of equity capital.